The armed forces modernization from across the procurement (2013)
We evaluated the proposed modernization of the military, based on the need to be at the forefront of new technologies that emerge from the current conflicts at national and international conflict, safety conditions in the world today involve the promotion and defense of peace internationally. The country must be prepared to assume, with its military , participation and support tasks on missions that are late to the tasks of the military or national defense approaches , for these purposes must be in the hand of the figure state contract , which was designed so that civil servants can to make contracts and the implementation thereof, the entities meet the governmental objective , continuous and efficient delivery of public services and the effectiveness of the rights and interests of the taxpayers who work with them in achieving those goals.